Quantification of long cane usage characteristics with the constant contact technique. (July 2016) - Kim, Yeongmi; Moncada-Torres, Arturo; Furrer, Jonas; Riesch, Markus; Gassert, Roger
Abstract: While a number of Electronic Travel Aids (ETAs) have been developed over the past decades, the conventional long cane remains the most widely utilized navigation tool for people with visual impairments. Understanding the characteristics of long cane usage is crucial for the development and acceptance of ETAs. Using optical tracking, cameras and inertial measurement units, we investigated grasp type, cane orientation and sweeping characteristics of the long cane with the constant contact technique. The mean cane tilt angle, sweeping angle, and grip rotation deviation were measured. Grasp type varied among subjects, but was maintained throughout the experiments, with thumb and index finger in contact with the cane handle over 90% of the time. We found large inter-subject differences in sweeping range and frequency, while the sweeping frequency showed low intra-subject variability. These findings give insights into long cane usage characteristics and provide critical information for the development of effective ETAs. Highlights: Cane usage characteristics show deviation from mobility skill training. Grasp type shows large inter-subject variability but low intra-subject variability. Roll angle range of a cane small to integrate a sensor on a long cane.